Evaluation of myocardial function in neonatal sepsis using tissue Doppler imaging. (16th November 2020) - Fahmey, Sameh S.; Hodeib, Mahmoud; Refaat, Khaled; Mohammed, Walaa
Abstract: Background: Neonatal sepsis is an important cause of neonatal morbidity and mortality especially in developing countries. Cardiac dysfunction is a major complication of severe sepsis and occurs as a part of multiple organ failure. Objective: To asses right and left ventricular functions in neonates with sepsis using tissue Doppler imaging (TDI). Methods: A total of 50 neonates fulfilling the diagnostic criteria for sepsis and 25 healthy neonates were enrolled in our study. Myocardial function and pulmonary systolic pressure were assessed using conventional echocardiography and tissue Doppler imaging techniques. Results: Septic neonates had a lower E/A ratio of the mitral valve when compared to healthy neonates ( p  = .048), indicating left ventricular diastolic dysfunction. Pulmonary systolic pressure was significantly higher in septic neonates compared to control group ( p  < .001). Left ventricular systolic function (left ventricular fractional shortening and S wave mitral annulus) was not significantly different between septic and healthy neonates. Left ventricular fractional shortening (LVFS) was found to be significantly higher in the survived than the nonsurvived septic neonates ( p  = .0387). Conclusions: Neonates with sepsis have evidence of left ventricular diastolic dysfunction and elevated pulmonary systolic pressure. Reduced left ventricular fractional shortening is associated with poor prognosis.